2018
DOI: 10.1186/s13287-018-1071-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo potentialities for cartilage repair from human advanced knee osteoarthritis synovial fluid-derived mesenchymal stem cells

Abstract: BackgroundMesenchymal stem cells (MSCs) are found in synovial fluid (SF) and can easily be harvested during arthrocentesis or arthroscopy. However, SF-MSC characterization and chondrogenicity in collagen sponges have been poorly documented as well as their hypothetical in vivo chondroprotective properties with intra-articular injections during experimental osteoarthritis (OA).MethodsSF-MSCs were isolated from human SF aspirates in patients suffering from advanced OA undergoing total knee joint replacements. SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 72 publications
1
70
0
Order By: Relevance
“…In contrast, and as expected, ECM synthesis was more pronounced on D56 and the densitometry measurements after ECM staining confirmed the benefit of combining TGF-β1 and BMP-2 [75,[84][85][86][87]. As we previously reported in a study of synovial fluid MSCs, we observed no influence of BMP-2 alone on both gene and protein levels [37]. Unfortunately, the phenotype of MSCs in cartilage repair is unstable so that differentiation continues along the endochondral ossification pathway.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…In contrast, and as expected, ECM synthesis was more pronounced on D56 and the densitometry measurements after ECM staining confirmed the benefit of combining TGF-β1 and BMP-2 [75,[84][85][86][87]. As we previously reported in a study of synovial fluid MSCs, we observed no influence of BMP-2 alone on both gene and protein levels [37]. Unfortunately, the phenotype of MSCs in cartilage repair is unstable so that differentiation continues along the endochondral ossification pathway.…”
supporting
confidence: 88%
“…Five-micrometer sections were cut and stained using Immunohistochemistry analyses were performed with the LSAB®+ kit (HRP, Dako) using anti-type II collagen monoclonal antibodies (Labvision, France). Paraffin-embedded tissues (5 μm) were deparaffinized, treated with pepsin (0.4% w/v, Sigma) for 30 min at room temperature, and incubated with a hydrogen peroxide blocking solution for 5 min to block the endogenous peroxidases, as precisely described in our previous work [37]. The sections were counterstained with hematoxylin and mounted with resin.…”
Section: Histological Evaluation Of Ecm Synthesized Inside 3d-mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite many positive findings, results have not been consistent in the literature. Neybecker et al 48 used an anterior cruciate ligament transection (ACLT) model in a rat, followed by injection of human SF-MSC into the rat's knee joint. The results showed no significant differences in the articular lesions in the ACLT-induced OA in the nude rat knee following a single SF-MSC injection.…”
Section: Animal Studies Of Sf-mscmentioning
confidence: 99%
“…Synovial fluid samples were diluted in expansion culture medium 1:6, then plated in Petri dishes. (21) MSCs were expanded in proliferation medium containing Dulbecco's modified Eagle's medium with low glucose (DMEM-LG, Gibco) with addition of 10% fetal bovine serum (FBS, Sigma), 1 ng/ml basic fibroblast growth factor (bFGF, Miltenyi Biotec), 1% glutamine (Gibco), and 1% penicillin-streptomycin (Gibco). Then they were cultured at 37°C with 5% humidified CO 2 .…”
Section: Isolation and Expansion Of Mscsmentioning
confidence: 99%